Prior residence and body size influence interactions between black sea urchins - Morishita, Vanessa Rimoli [UNESP]; de Carvalho Buchmann, Francisco Sekiguchi [UNESP]; Christofoletti, Ronaldo Adriano; Volpato, Gilson Luiz [UNESP]; Barreto, Rodrigo Egydio [UNESP] (Elsevier B.V., 2009)
Body size and prior residence can modulate agonistic interaction in several animal species, but scientists know little about these relationships in echinoderms. In this study, we tested the effects of these traits on interactions in the black sea urchin (Echinometra lucunter). After a sea urchin was isolated for 24-h in a glass tank to establish prior residence, we introduced an intruder animal adjacent to the resident in the tank and observed interactions for 30 min. The intruder animal was larger, smaller, or size-matched to the resident. We found body size and prior residence concomitantly modulated interactions among black sea urchins, with prior residence as the major determinant. Black sea urchins mainly exhibited opponent inspection and fleeing responses during interaction to avoid fights, especially when a fight could be seriously disadvantageous (small intruder vs. large resident). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Echinometra lucunter; Echinoderms; Fighting asymmetry; Aggression